Controlling Work Stress: Effective Human Resource and Management StrategiesControlling Work Stress: Effective Human Resource and Management Strategies, by MattesonM. T. and IvancevichJ. M.. San Francisco: Jossey Bass Publishers, 1987, 378 $25.95 pp., cloth. - Wilhelm, Paul G. (Academy of Management Review, 1989)
The article reviews the book “Controlling Work Stress: Effective Human Resource and Management Strategies,” by M.T. Matteson and J.M. Ivancevich.